“Kancil the Mousedeer of Sumatra” and “Kancil Saves the Rainforest of Sumatera”: an American Perspective - Eddy Pursubaryanto (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2009)
Tulisan ini melihat bagaimana Tamara Fielding, seorang story teller dari Amerika, menyajikan dua episode cerita kancil versi Indonesia lewat acara TV